ASSESSMENT OF STARCH FREE CISSUS POPULNEA POLYMER AS SUSPENDINGAGENT IN PARACETAMOL SUSPENSION - MATHIAS, IJI E.; JENNIFER, AUDU-PETER D.; NEP E IRMYA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
The suspending properties of mucilage of starch free Cissus populnea (sfCPP) were evaluatedcomparatively with those of the native Cissus populnea (nCPP), and tragacanth in paracetamolsuspension. The gums were used in concentrations of 0.5 to 3.0 % w/v. The sedimentation rates,sedimentation volume, ease of re-dispersibility and viscosity of the suspension were studied asassessment parameters. The rank order of the suspending ability of the suspending agents asevaluated by the sedimentation volume was sfCPP> nCPP> tragacanth. Paracetamol suspensionshaving sfCPP has significantly higher viscosity (p<0.05) when compared with those of nCPP,and tragacanth. The flow rate decreases with increase in the concentration of the suspendingagent and viscosity. The viscosity of formulations containing sfCPP decreases with increasedspeed of agitation which confers good characteristic of suspension. On the basis of these findings,pharmaceutical suspension containing sfCPP as suspending agent having the highestperformance when compared to nCPP and tragacanth may preferably be applied as liquid drugdelivery system for paediatric patients.